Non-cardioembolic stroke/transient ischaemic attack in Asians and non-Asians: a post-hoc analysis of the PERFORM study - Hoshino, Takao; Sissani, Leila; Labreuche, Julien; Bousser, Marie-Germaine; Chamorro, Angel; Fisher, Marc; Ford, Ian; Fox, Kim M.; Hennerici, Michael G.; Mattle, Heinrich P.; Rothwell, Peter M.; Steg, Philippe Gabriel; et al. (European stroke journal, 2019)
IntroductionWe aimed to compare the characteristics and vascular outcomes between Asian and non-Asian patients with non-cardioembolic stroke/transient ischaemic attack receiving antiplatelet monoth...
First published August 24, 2018
Gesehen am 18.06.2020